True green @ work : 100 ways you can make the environment your business - McKay, Kim.; Bonnin, Jenny; Wallace, Tim. (Washington, D.C. : National Geographic Society, 2008)
Presents 100 strategies for safeguarding the environment.
Originally published: Sydney : ABC Books for the Australian Broadcasting Corporation, 2007.
Includes bibliographical references (p. 132-135)
Keywords: Consumption (Economics); Environmentalism; Conservation of natural resources; Environmental responsibility; Management; Business enterprises; Social responsibility of business